2012
DOI: 10.1111/j.1440-1843.2012.02195.x
|View full text |Cite
|
Sign up to set email alerts
|

Does outdoor air pollution induce new cases of asthma? Biological plausibility and evidence; a review

Abstract: It is widely accepted that air pollution can exacerbate asthma in those who already have the condition. What is less clear is whether air pollution can contribute to the initiation of new cases of asthma. Mechanistic evidence from toxicological studies, together with recent information on genes that predispose towards the development of asthma, suggests that this is biologically plausible, particularly in the light of the current understanding of asthma as a complex disease with a variety of phenotypes. The ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
119
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(126 citation statements)
references
References 68 publications
2
119
0
5
Order By: Relevance
“…Other studies, however, did not find any association, which could be due to differences in study design in terms of case definition and exposure assessment, populations, and periods of survey [5,6]. Overall, our colleagues in the UK suggested that the evidence is consistent with the possibility that outdoor air pollution might play a role in causing asthma in susceptible individuals living very close to busy roads carrying heavy lorry traffic [7], which is supported by increasing evidence in Europe and elsewhere. Notably, the observed odds ratios were not elevated (unlike the risk of lung cancer from smoking tobacco, for example), which can be explained by the fact that asthma is a multifactorial disease and is dependent on the simultaneous occurrence of several exposures to both genetic and environmental factors [8].…”
supporting
confidence: 70%
“…Other studies, however, did not find any association, which could be due to differences in study design in terms of case definition and exposure assessment, populations, and periods of survey [5,6]. Overall, our colleagues in the UK suggested that the evidence is consistent with the possibility that outdoor air pollution might play a role in causing asthma in susceptible individuals living very close to busy roads carrying heavy lorry traffic [7], which is supported by increasing evidence in Europe and elsewhere. Notably, the observed odds ratios were not elevated (unlike the risk of lung cancer from smoking tobacco, for example), which can be explained by the fact that asthma is a multifactorial disease and is dependent on the simultaneous occurrence of several exposures to both genetic and environmental factors [8].…”
supporting
confidence: 70%
“…COMEAP recently concluded that the epidemiological evidence for associations between ambient levels of air pollutants and asthma prevalence at a whole community level was unconvincing; a meta-analysis confirmed a lack of association (Gowers et al, 2012). In contrast, a meta-analysis of cohort studies found an association between asthma incidence and within-community variations in air pollution (largely traffic dominated).…”
Section: Rationalementioning
confidence: 95%
“…A similar meta-analysis with 19 studies conducted exclusively in children found a statistically significant association between the incidence of childhood asthma and NO 2 (OR, 1.14; 95% CI, 1.06-1.24, per 10-mg/m 3 increase) (16). A review of these and other studies concluded that traffic-related pollution may play a role in the development of asthma, especially in individuals living near highvolume roadways (25).…”
mentioning
confidence: 96%